Screening of Hirsutum Cotton Genotypes for Drought Tolerance under Different Osmotic Potential and Field Capacities - B. R., Megha; Mummigatti, U. V. (International Journal of Bio-resource and Stress Management, 2017)
A Lab experiments were conducted during 2016 at Agriculture Research Station, Crop physiology division, Hebballi farm, UAS, Dharwad, to screen twenty one cotton genotypes under water stress condition for seed germination and seedling growth. Study consisted of 19 Gossypium hirsutum genotypes with three checks (LRA-5166 (National check), RAH-100 (Zonal check) and Sahana (Regional check)). Seed germination and seedling growth study was conducted under different osmotic potentials using PEG- 6000 (0.0 MPa), −0.140 MPa and −0.39 MPa and pot study with different moisture levels (100, 50 and 25% field capacity). Results indicated that as the PEG concentration and stress level increases, the root length, root weight, lateral root number, proline content increased and chlorophyll content decreased. Whereas, shoot biomass decreased resulting in increase in root to shoot ratio. The varieties viz., Sahana, BS-37, LRA-5166, CCH-12-3, GBHV- 177, BS-39, GBHV-182, ARBH-1352, which showed higher seedling indices like seedling vigor index, shoot vigor index, and root vigor index under higher osmotic potential and moisture stress condition and can be considered as drought tolerant varieties based on seed germination and seedling growth studies and the genotypes viz., RAH-100, RAH-806, GSHV-169, AHK-09-05, NDLH-1943, NDLH-1938 were considerd as a less tolerant genotypes due to decrease in the germination %, seedling indices, root to shoot ratio, morphological characters, proline content, chlorophyll content of cotton plants under different PEG concentration and field capacity.